Perspectives of CB1 Antagonist in Treatment of Obesity: Experience of RIO-Asia. (29th December 2010) - Pan, Changyu; Yoo, Hyung Joon; Ho, Low-Tone
Abstract : Rimonabant, a selective cannabinoid-1 (CB1) receptor antagonist, has been shown to reduce weight and enhance improvements in cardiometabolic risk parameters in Western populations. This study assessed these effects of rimonabant in Asian population. A total of 643 patients (BMI 25 kg / m 2 or greater without diabetes) from China, Republic of Korea, and Taiwan were prescribed a hypocaloric diet (600 kcal/day deficit) and randomized to rimonabant 20 mg (n = 318 ) or placebo (n = 325 ) for 9months. The primary efficacy variable was weight change from baseline after 9 months of treatment. Results showed that rimonabant group lost more weight than placebo, (LSM ± SEM of −4.7 ± 0.3 kg vs. −1.7 ± 0.3 kg, P < .0001 ). The 5% and 10% responders were 2 or 3 folds more in the rimonabant group (53.0% vs. 20.0% and 21.5% vs. 5.7%, resp.) (P < .0001 ). Rimonabant also significantly increased HDL-cholesterol, decreased triglycerides and waist circumference, by 7.1%, 10.6%, and 2.8 cm, respectively (P < .0001 ). This study confirmed the comparable efficacy and safety profile of rimonabant in Asian population to Caucasians. Owing to the recent suspension of all the CB1 antagonists off the pharmaceutical market for weight reduction in Europe and USA, a perspective in drug discovery for intervening peripheral CB1 receptor in the management of obesity is discussed.